Gonad RNA-specific qRT-PCR analyses identify genes with potential functions in schistosome reproduction such as SmFz1 and SmFGFRs - Hahnel, Steffen; Quack, Thomas; Parker-Manuel, Sophia J.; Lu, Zhigang; Vanderstraete, Mathieu; Morel, Marion; Dissous, Colette; Cailliau, Katia; Grevelding, Christoph G. (Frontiers in Genetics, 2014)
In the search for new strategies to fight schistosomiasis, the unique reproductive biology of Schistosoma mansoni has come into the focus of research. The development of the gonads and the ability of egg production are fundamental not only for continuing the life cycle but also for pathogenicity. Previous studies of schistosome biology demonstrated an influence of pairing on gonad development of the female and on gene expression profiles in both genders. Due to the limited access to specific tissues, however, most of these studies were done at the level of whole worms neglecting individual tissues that may be targets of pairing-dependent processes. Recently, we established a protocol allowing the isolation of testes and ovaries from adult S. mansoni. Here, we describe tissue-specific qRT-PCR analyses comparing transcript levels of selected genes on the basis of RNA from gonads and whole worms. Gene expression in ovary and testes was in some cases found to be significantly influenced by pairing, which was not traceable in whole worms. Among the candidate genes identified as regulated by pairing in gonads were the frizzled homolog SmFz1 and the two fibroblast growth factor receptor homologs SmFGFR-A and SmFGFR-B. First functional characterizations were done, including comparative qRT-PCR analyses, in situ-localization experiments, heterologous expression in Xenopus oocytes (SmFGFR-A/B), and inhibitor studies using the Fz/Dvl-pathway inhibitor 3289-8625, or BIBF1120 blocking FGFR-signaling. Besides confirming gonad localization and receptor functions, inhibitor-induced phenotypes were observed in vitro such as decreased egg production as well as drastic effects on gonad differentiation, morphology, embryogenesis, and survival of adult worms. In summary, these results emphasise the usefulness of tissue-specific qRT-PCRs for selection of candidate genes with important roles in reproduction, allowing subsequent studies to determine their suitability as drug targets.